The Naturalist Theatrical Aesthetic of Bottle Episodes. Issue 3 (1st January 2014) - Nannicelli, Ted
Abstract: This article identifies and describes a special sort of television episode known as a 'bottle episode'. After characterising the typical features of bottle episodes, the article proceeds to investigate the following question: What narrative strategies and stylistic techniques do practitioners adopt to cope with the practical constraints imposed by bottle episodes? The answer, advanced and defended in the later portion of the article, is that a typical solution is for practitioners to embrace a 'Naturalist theatrical aesthetic'.